1997
DOI: 10.1021/jp962245x
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of a Faujasite Y as a Function of the Hydration State

Abstract: The evolution of conduction and polarization phenomena is studied as a function of dehydration temperature (TT varying from 100 up to 400 °C) on a faujasite Y zeolite. The measurements are carried out as a function of frequency at different temperatures. In all cases, the conductivity is ascribed to the migration of cations in large cages involving energies varying from 0.61 to 0.85 eV. Two relaxation domains are observed. It is assumed that they are due to the movement of cations of sites III‘ and II. The exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…These results obviously indicate that the water molecules adsorbed at the grain boundary strongly influence the dc conductivity. This behavior is well known and has already been reported in clays [19] and in aluminosilicates as zeolites [20,21]. It points out that the dc conductivity is related to ionic motion since water does not usually influence the conductivity of electronic semiconductors much.…”
Section: Conductivitysupporting
confidence: 67%
“…These results obviously indicate that the water molecules adsorbed at the grain boundary strongly influence the dc conductivity. This behavior is well known and has already been reported in clays [19] and in aluminosilicates as zeolites [20,21]. It points out that the dc conductivity is related to ionic motion since water does not usually influence the conductivity of electronic semiconductors much.…”
Section: Conductivitysupporting
confidence: 67%
“…In addition, seven water sites are known. Previous electrical studies on zeolites have shown that the electrical conductivity, along with dielectric relaxation phenomena in zeolites, are strongly affected by the presence of adsorbed water [16][17][18] . However, after dehydration, it is expected that any measured conductivity will be due to the migration of interstitial cations, commonly alkali metal or alkaline earth metal cations [19][20][21].…”
Section: Position Of Caption For Figure 1a and 1bmentioning
confidence: 99%
“…Upon inclusion of water within the chabazite pores, the interaction of the cations with the anionic framework becomes weaker and the cations become more mobile in the applied electric field. Many authors have shown that residual water in the pores of zeolites can lead to increased conductivity [16,17].…”
Section: Electrical Properties During Heatingmentioning
confidence: 99%
“…7), has been ascribed to the motion of cations in sites IIr [29,30]. The relaxation connected with peak 2 has been assigned to the motion of cations of sites II [29,30].…”
mentioning
confidence: 93%